A cartography of Antonio Gramsci's pedagogical itinerary between Italy and Latin America (1968-1991). Disparate effects of the crisis of Marxism (Praxis Educativa, 2024)
The article deals with Antonio Gramsci's itinerary in the Italian and Latin American pedagogical field between 1968 and 1991, that is, between the protest movements of 1968 and the dissolution of the USSR. The most dynamic phase of the educational study of the Sardinian in the peninsula occurred between 1968 and 1976, while in Latin America it took place from the mid-1970s to 1991. As a hypothesis, it is suggested that the crisis of Marxism in the 1970s had disparate effects on the two regions and on the pedagogical study of the sardinian: in Italy it provoked a retraction, but in Latin America, intellectuals continued to reflect within the paradigm in crisis and resorted to Gramsci to renew educational research. The article concludes that the regime of Gramsci's pedagogical circulation between the two regions during the period was not exempt from a double condition: center-periphery dynamics and a patriarchal logic.
Keywords: Antonio Gramsci; education; crisis of Marxism; Italy; Latin America